PERENCANAAN STRATEGIS SISTEM INFORMASI MENGGUNAKAN METODE ENTERPRISE ARCHITECTURE PLANNING (EAP) PADA KANTOR KETAHANAN PANGAN KABUPATEN SAROLANGUN - Tamala, David; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2020)
Food Security is a organizer that assists policy, development, monitoring food availability, strengtheningfood distribution, establishing consumption patterns, monitoring market food security, and foodadministration. At present, in the Sarolangun District Food Security office, information system strategicplanning has not yet been implemented such as CPCL receipts, distribution of production facilities,assistance and evaluation, financial management, human resource management and facilities andinfrastructure management. Implementation is only carried out based on the needs of the vulnerability spacewhich is limited to the interests of the agency without any overall planning and only for one particularfunction of the organization. The activities carried out in each of these fields are assisted by computers byusing Microsoft Excel and Microsoft Word to process data as this results in information systems not beingintegrated between one field and another. With this, information system strategic planning is needed in theapproach used is enterprise architecture planning. This study resulted in planning a form of blueprintregarding information organization in the form of enterprise architecture that can be used to support policystrategies in the development of an organized and integrated system in the Sarolangun District Food Securityoffice